OVERVIEW SELF EFFICACY OF SPIRITUAL AND PATIENTS HIV/AIDS IN THE PROVINCE BENGKULU - Ismatul Zahara; Sardaniah Sardaniah; Tuti Anggriani Utama (Jurnal Vokasi Keperawatan (JVK), 2021)
Our objective is to see the picture of self-efficacy, and the level of  spirituality of HIV / AIDS patients in Bengkulu Province. The results of this study can be used  to increase the client's knowledge about the importance of self-efficacy, and  spiritual level of the HIV / AIDS patient itself. Its Benefits As an ingredient  consideration for further research as well as motivating researchers to  read the latest issues and trends regarding HIV / AIDS, especially in the Province  Bengkulu. using this type of descriptive research in order to explain  how to describe self-efficacy and spiritual level in HIV / AIDS patients at  Bengkulu Province. (Nursalam 2008, in Henni, 2011) The population in this study  are all HIV / AIDS positive clients, amounting to 177 people in the Province  Bengkulu.used was Thepurposive sampling sample123  people were sampled with certain criteria (Hardani, 2020). The results show  most PLHIV in Bengkulu Province in this study have self  efficacy sufficientthat about 24 out of 50 respondents enter into it  category of ODHA with Self Efficacy sufficient. and on spiritual variables  some ODHA respondents in Bengkulu Province have a high spiritual level  where this is supported by the results of the study that of the 50 respondents 41 people  fall into the category of a high spiritual level. The benefits of research can be  additional literature for nursing institutions regarding aspects of self-efficacy and  spiritual in order to create a characteristic nurse. ODHA is expected to  increase knowledge about Self Efficacy and Spiritual level in order to be able  optimize existing support and guidance resources. Researchers hope  there is further research related to other factors that affect health  especially for people living with HIV / AIDS. .